Gene Expression Changes in Steroid-Induced IOP Elevation in Bovine Trabecular Meshwork - Danias, John (Association for Research in Vision and Ophthalmology, Inc., 2011)
PURPOSE. To determine whether gene expression changes occur in the trabecular meshwork (TM) of cow eyes with steroid-induced intraocular pressure (IOP) elevation. METHODS. Adult female Braford cows (n = 4) were subjected to uniocular prednisolone acetate treatment for 6 weeks. IOP was monitored with an applanation tonometer. At the conclusion of the experiment, animals were euthanized, eyes were enucleated, and the TM was dissected and stored in an aqueous nontoxic tissue storage reagent. RNA was extracted and subjected to microarray analysis using commercial oligonucleotide bovine arrays. Some of the genes differentially expressed between control and experimental eyes were confirmed by quantitative RT-PCR and some of the respective proteins were studied by immunoblotting. RESULTS. IOP began to increase after 3 weeks of treatment, reaching a peak 2 weeks later. IOP differences between corticosteroid-treated and fellow control eyes were 6 ± 1 mm Hg (mean ± SD) at the conclusion of the study. Microarray analysis revealed that expression of 258 genes was upregulated, whereas expression of 187 genes was downregulated in the TM of eyes with steroid-induced IOP elevation. Genes identified to be differentially expressed include genes coding for cytoskeletal proteins, enzymes, growth and transcription factors, as well as extracellular matrix proteins and immune response proteins. A number of relevant gene networks were detected by bioinformatic analysis. CONCLUSIONS. Steroid-induced IOP elevation alters gene expression in the bovine TM. Identification of genes with changing expression in this model of open-angle glaucoma may help elucidate the primary changes occurring at the molecular level in this condition.